Measurement and simulation of partial discharge activity within a void cavity in a polymeric power cable model - Illias H.A.; Othman M.E.; Tunio M.A.; Bakar A.H.A.; Mokhlis H.; Chen G.; Lewin P.L.; Ariffin A.M. (2023)
In high voltage power cable, partial discharge (PD) phenomenon may occur within defects that exist in its insulation system. The insulation is normally made of a dielectric material, typically polymeric materials. Repetition of PD activity at the defect site may cause insulation breakdown when the defect grows until it bridges the electrodes between the insulation. Consequently, breakdown of the whole cable will occur. Thus, measurement of PD activity within cable insulation system has been extensively used to monitor the condition of power cables in service. A void cavity is one of the most common PD sources when a cable insulation is stressed under high electric field. In this work, measurements of PD activity within an artificial cylindrical void in the insulation layer of a 22 kV cross-linked polyethylene (XLPE) cable was performed. A two-dimensional model of a cable insulation geometry with a void was also developed using finite element analysis (FEA) software. The model was used to calculate the electric field magnitude in the void within the cable insulation under different conditions of voids and insulation. From this work, an understanding on PD phenomenon within a cylindrical void in a power cable insulation can be enhanced. 2013 IEEE.